Vision Therapy for Oculomotor Dysfunctions following Mild TBI: A Case Report. - Rooms, Kim (Optometry & Visual Performance, 2024)
Background: Oculomotor dysfunctions are common visual problems following mild traumatic brain injury (TBI). They not only produce vision discomfort and possible loss of visual efficiency, but they may also negatively affect the overall rehabilitative process. It is important for clinicians to be aware of the visual symptoms and the possible treatments for oculomotor dysfunctions. Case Report: A 44-year-old TBI patient with complaints of blurred near vision, visual discomfort, and reduced peripheral vision was examined. He was diagnosed with fusional vergence dysfunction and saccadic dysfunction. The treatment consisted of eight in-office vision therapy sessions every one to two weeks and daily home exercises. The post-treatment examination showed increased vergence ranges, improved stereopsis, and better saccadic function. The patient reported a reduction in visual complaints. Conclusion: This case report indicates that officebased vision therapy is effective in reducing visual symptoms and improving oculomotor dysfunctions after mild traumatic brain injury.